PERSEPSI MAHASISWA PENDIDIKAN SEJARAH TERHADAP TUGAS SEJARAH LISAN DI PROGRAM STUDI PENDIDIKAN SEJARAH FKIP UNTAN - Evi Evi; Rustiyarso Rustiyarso; Andang Firmansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe students' perceptions about the task of learning oral history in the FKIP Untan History Education Study Program. This research uses qualitative methods with a descriptive approach. The data collection techniques used were observation, interview and documentation. Data collection tools are observation guidelines, interview guides, documentation tools. The data analysis technique used is analysis before in the field and data analysis while in the field. Testing the validity of the data, namely using extended observations, increasing persistence and triangulation consisting of triangulation of sources, triangulation of techniques and triangulation of time. Based on the results of the research (1) The task of oral history is to look for historical places / events and more detailed knowledge by interviewing people who understand the place or can also look for people who are involved in historical events. (2) The forms of tasks given in general, such as interviewing sources, making observations, preparing question instruments to informants, making reports or papers, presentations, power points, doing group assignments, individual daily assignments, then for the final assessment given uts and uas. (3) First, in doing the assignments, students experience difficulties, such as the literature in the library is still minimal. Both facilities and infrastructure also affect learning in classrooms with heat and lack of chairs and tables, it also disturbs student learning concentration. These three covid19 periods are required by the public or students to stay at home and study online.Keywords: Perception, Students, Oral History Assignments